In Vivo Evaluation of Wound Healing and Anti-Inflammatory Activity of 80% Methanol Crude Flower Extract of Hagenia abyssinica (Bruce) J.F. Gmel in Mice - Belachew, Teshome Fentik (Evid Based Complement Alternat Med, 2020)
BACKGROUND: Hagenia abyssinica (Bruce) J.F. Gmel (Rosaceae) is distributed in the highlands of Ethiopia. The flowers of Hagenia abyssinica (Bruce) J.F. Gmel are used traditionally to treat wound. However, there was no scientific report on wound healing activity of Hagenia abyssinica (Bruce) J.F. Gmel. Thus, this study was initiated to investigate the wound healing and anti-inflammatory activities of 80% methanol crude extract of flowers of Hagenia abyssinica in mice. OBJECTIVE: The objective of this study was to evaluate the wound healing and anti-inflammatory activity of 80% methanol crude flower extract of Hagenia abyssinica in mice. METHODS: Air-dried flowers of Hagenia abyssinica were grounded and macerated three times successively by 80% methanol. The dried extract was fractionated with chloroform, ethyl acetate, and water. Phytochemical screening tests were performed according to established procedures. The crude extract and solvent fractions were formulated as ointments. Wound healing activity of the crude extract was evaluated using excision and incision wound models, and the wound healing activities of solvent fractions were evaluated by using the excision wound model. The anti-inflammatory activity of the 80% methanol extract of Hagenia abyssinica was evaluated using carrageenan-induced hind paw edema model in mice. RESULT: The 2000 mg/kg test dose of the 10% (w/w) crude extract ointment was safe in rats. Both the 5% (w/w) and 10% (w/w) crude extract ointment-treated groups showed significant wound contraction starting from the day 4(th). Both 5% (w/w) and 10% (w/w) crude extract ointments showed significant (P < 0.001) increment of tensile strength compared to the negative control. The 10% (w/w) aqueous and ethyl acetate fraction ointment revealed high (P < 0.001) percentage of wound contraction. The 100 mg/kg, 200 mg/kg, and 400 mg/kg oral administration of the crude extract had significant inhibition of the paw edema in mice of carrageenan-induced inflammation. CONCLUSION: The results of this study evidenced that both 5% w/w and 10% w/w 80% methanol extract ointment of the flowers of Hagenia abyssinica have wound healing and anti-inflammatory effects.